Portable Small Items Stair-Lift (Detachable) - Nawi, I.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Loss of balance leads to the increasing numbers of stair falls experienced by elderly people. To help eliminate the hardships faced by elderly people from lack of balance, a portable small items stair-lift was developed. The prototype will have the ability to carry small items up and downstairs through the stair handrails. This reduces the risk faced by elderly people while going up and down. The key feature of this prototype is its portability, which differentiates it from other already available products in the market serving a somewhat similar purpose. The portable stair-lift is being controlled wirelessly through a developed user interface via Wi-Fi network. A live video streaming of the device view is also included which permits control for not only users nearby but even those away from home to help if in any case the people that are about to use it is incapable. Overall, this device will aid in increasing the safety aspects of stairs and promotes further advancement towards the quality of life in general. Â© 2021 IEEE.